ANALISIS PEMASARAN GETAH DAMAR DI DESA MALINO JAYA KECAMATAN SOYO JAYA KABUPATEN MOROWALI UTARA - Santosa, Tri Mohamad; Kassa, Saharia; Laapo, Alimudin (AGROTEKBIS, 2016)
Indonesia is an archipelago located in the equatorial region and is known as one of the nationâs largest owner of forest products in the world, one of which is a resin. The forestry sector marketing activities of forest product is an economic activity that play a role linking the interest of producers (tapper) with consumer. Marketing result are expected to provide a proportional benefit to producers and actors in accordance with the marketing cost, risks and sacrifices that have been issued. The purpose of this research was to determine is the form of marketing channel, the amount of the marketing margin resin in each marketing channel, the part of the price received by the tapper (producer) resin in each marketing channel, and the marketing efficiency gum resin in each marketing channel.This research was conducted in the village of Malino Jaya Soyo Jaya District North Morowali in May to August 2015. Tapper take as much as 34 respondents drawn from the entire population. In addition, to determine the respondent merchant totalling 3 respondent used Tracing Sampling Method.The result of analysis showed the gum resin marketing channels in the village of Malino Jaya Soyo Jaya District North Morowali Country consists of 2 channels, namely :Tapper â Traders â Wholesalers â Custumers (Exporters)Tapper â Wholesalers â Custumers (Exporters)Total marketing margin of the gum resin in the marketing channel I is Rp. 3.100,00/kg and the marketing margin resin on marketing channel II is Rp. 2.100,00/kg. The part of prices received by farmer on channel I at 77,21% and the part of the price received by farmer on channel II at 81,56%. On both of the marketing channel, the marketing channel II more efficienctly than the marketing channel I, because the ratio between the price received by the custumers with the total marketing cost per kilogram on channel II at 38,75 , higher than the channel I is 34,57.Â Key Words: Gum Resin. marketing channel, marketing margin, marketing efficiency.Â